DIALEKTIKA RELASIONAL PEREMPUAN BALI DALAM PERKAWINAN NYEROD: ANALISIS KOMUNIKASI PADA MASYARAKAT URBAN DENPASAR - AA Ayu Carnesya Cipta Resmi Bilton; Ni Putu Bayu Widhi Antari; I Nyoman Subanda; Nuning Indah Pratiwi (Journal of Innovation Research and Knowledge, 2025)
This research aims to examine the dialectical dynamics of communication experienced by Balinese women in the practice of nyerod marriage, namely inter-caste marriage where women from the Tri Wangsa caste marry men from the Sudra caste. Nyerod's marriage represented a continuing tension between hierarchical customary values and the modernization process in social structures. This research uses a descriptive qualitative approach with relational dialectical theory as an analytical knife to understand the conflicting values, identities and self-negotiations of women in the context of nyerod marriage. Data was obtained through in-depth interviews with five female Nyerod perpetrators, one piscologist and one Hindu religious academic in Pemecutan Kaja Village, Denpasar City who were selected purposively. The results of the research show that Balinese women who carry out Nyerod marriages are awakened through three main dialectical arenas, namely intrapersonal conflict as a negotiation between certainty and uncertainty of identity and the future, societal stigma as a tug-of-war between freedom of choice and social hierarchy, and language change as a medium of interaction in everyday life. Women not only experience structural stress, but also actively negotiate their identity and position through adaptation strategies and acceptance of consequences. This research contributes theoretically to the need to apply relational dialectical theory to the Balinese cultural context, and practically provides a critical understanding of the dynamics of communication, gender and social transformation in Nyerod marriage.